2014
DOI: 10.1128/iai.00855-13
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Surfactant Protein D, Interleukin-5, and Eosinophilia on Cryptococcosis

Abstract: Cryptococcus neoformans is an opportunistic fungal pathogen that initiates infection following inhalation. As a result, the pulmonary immune response provides a first line of defense against C. neoformans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 49 publications
(48 reference statements)
1
41
0
Order By: Relevance
“…As an example, SP-D-deficient mice infected with the fungus Cryptococcus neoformans (CN) have decreased pulmonary eosinophils and lower IL-5 levels in lung lavage fluid compared with control wild-type (WT) mice. Moreover, CN-infected SP-D mice have decreased fungal burden and improved survival compared with the WT controls (20). These findings support the concept that SP-D is a virulence factor for CN and facilitates its infection in mice.…”
Section: Roles Of Sp-a/-d In Cell-mediated Immunitysupporting
confidence: 76%
See 1 more Smart Citation
“…As an example, SP-D-deficient mice infected with the fungus Cryptococcus neoformans (CN) have decreased pulmonary eosinophils and lower IL-5 levels in lung lavage fluid compared with control wild-type (WT) mice. Moreover, CN-infected SP-D mice have decreased fungal burden and improved survival compared with the WT controls (20). These findings support the concept that SP-D is a virulence factor for CN and facilitates its infection in mice.…”
Section: Roles Of Sp-a/-d In Cell-mediated Immunitysupporting
confidence: 76%
“…In addition, reactive oxygen and nitrogen species may also affect posttranslational modifications of SP-D that alter its structure and function at sites of inflammation (39,113). For example, NO, produced locally by airway epithelial cells and increased in asthma (114), has been shown to S-nitrosylate two free Cys thiols in the N-terminus of dodecameric SP-D (Cys- [15][16][17][18][19][20] and to affect dissociation into SP-D trimers (115). Consequences of this structural perturbation include the activation of SP-D proinflammatory chemoattractant function and the loss of control TLR4 blockade (39).…”
Section: Alterations Of Sp-a/-d In Eosinophil-predominant Diseasesmentioning
confidence: 99%
“…Eosinophils were associated with a lack of protection against C. neoformans in pulmonary infection model in which their presence was associated with excessive lung inflammation [91]. C57BL/6 mice develop eosinophilic pneumonia in response to pulmonary cryptococcal infection [92] and eosinophilia has also been observed in human cryptococcosis [93].…”
Section: Innate Immune and Cellular Responses To C Neoformansmentioning
confidence: 99%
“…Additionally, a recent study reported that SP‐D is responsible for IL‐5‐induced eosinophilic inflammation in Cryptococcus ‐infected mice (Holmer et al. ). Although the model is different to our allergic model, it partly explains decreased IL‐5 production and airway eosinophilia in SP‐D deficiency.…”
Section: Discussionmentioning
confidence: 99%